Effect of three defoliation frequency treatments and drought on perennial ryegrass herbage and root growth and water‐soluble carbohydrate reserves - Katherine N. Tozer; Rose M. Greenfield; Catherine A. Cameron; Martin P. Upsdell; David E. Hume (Grassland Research)
Abstract Background Grazing approaches are needed to increase the resilience of perennial ryegrass (Lolium perenne L.)‐based pastures subject to increasing drought stress. One opportunity has focused on seedhead management in late spring. Paddock‐level studies demonstrated increased pasture resilience when ryegrass seedheads are allowed to mature, but knowledge is lacking on how defoliation management affects plant carbohydrate status and hence resilience in the sward. Methods A glasshouse study was conducted from spring to autumn using 1 m deep root tubes. Plant growth and water‐soluble carbohydrate (WSC) reserves were measured every 4–6 weeks. Defoliation treatments comprised “VEGETATIVE”—regular defoliation based on leaf stage and trimmed to 4 cm; “FLOWERING”—no defoliation spring to anthesis; and “SENESCENT”—no defoliation spring to reproductive tiller senescence. Thereafter, regular defoliation was carried out for all treatments until the end of the study. From spring to the end of summer, plants were watered daily in WET (no drought, well watered) and on four occasions in DRY (drought) treatments, with daily watering thereafter. Results Herbage mass, tillering, root depth, root mass, and WSC were generally higher in SENESCENT than VEGETATIVE with FLOWERING intermediate (p < 0.05). Nutritive values were similar in VEGETATIVE and FLOWERING, but in SENESCENT, metabolizable energy and crude protein declined and neutral detergent fiber increased (p < 0.05). Soil moisture effects were small, with the DRY treatment resulting in moderate suppression of herbage growth and a minor reduction in WSC reserves (p < 0.05). Conclusions Results were consistent with field studies and recommendations to allow perennial ryegrass tillers to set seed to improve pasture resilience.